Hydrogen Gas Inhalation Regressed Coronary Artery Aneurysm in Kawasaki Disease-Case Report and Article Review - Kuo, Ho-Chang (Frontiers in Cardiovascular Medicine, 2022)
Kawasaki disease (KD) is a systemic vasculitis that primarily affects children under the age of 5 years old and is among the most common acquired heart disease in developed countries, particularly in Asia. No effective treatment is currently available for aneurysm formation in KD. In this report, we showed a KD patient with an aneurysm over the right coronary artery with a size of 6.08 mm in diameter and 35 mm in length, which completely regressed to within normal range after hydrogen inhalation within 4 months after disease onset. This 10-year-old KD patient was diagnosed on the 12th day of disease onset with incomplete presentation of KD symptoms. Intravenous immunoglobulin was prescribed after KD diagnosis was confirmed by the formation of a coronary artery aneurysm. Once discharged from the hospital, the family used hydrogen inhalation (77% hydrogen and 23% oxygen) at home with nasal cannula 1 h per day. The aneurysm was found to be completely regressed at the 4-month follow-up (day 138 of the illness). The follow-up laboratory data showed complete blood cell count, differential count, electrolytes, liver enzyme, and renal function to all be within normal range. This is the first study to report an aneurysm from KD with regression under supplementary therapy with hydrogen gas inhalation and no other complications. Therefore, hydrogen gas inhalation may be an alternative anti-free radical or anti-oxidant therapy for KD, but further study is still required.